Taking sides. Clashing views in adolescence - Drysdale, Maureen T.B.; Rye, B. J. (Barry John) (Dubuque, IA : McGraw-Hill, 2007)
[This text] is a debate-style reader designed to introduce students to controversies in adolescence. The readings, which represent the arguments of leading psychologists, adolescent health professionals, and commentators, reflect a variety of viewpoints and have been selected for their liveliness and substance and because of their value in a debate framework. -Back cover.
Adolescent health: Should adolescents be taking antidepressants?; Should adolescents be allowed to drink alcohol?; Should parental consent be required for adolescents seeking abortions?; Do boys worry about an ideal body image as much as girls do? -- Sex and sexuality: Should adolescents get comprehensive sex education outside the home?; Should adolescents have easy access to condoms in schools?; Is there cause for concern about an "oral sex crisis" for teens?; Is comprehensive sex education for adolescents too liberal?; Does sex on TV negatively impact adolescent sexuality?; Does a traditional or "strong" double standard with respect to sexual behavior exist among adolescents?; Female sexual orientation more fluid than male sexual orientation during adolescence? -- Relationships: Does divorce or disruption in family structure during adolescence have a detrimental effect on development?; Does dating impede developmental adjustment for adolescents?; Do cyber-friendships hinder healthy adolescent development? -- Antisocial behaviors: Should adolescents who commit serious offenses be tried and convicted as adults?; Is school-related violence increasing?; Are girls bigger bullies than boys?; Is the use of "club drugs" a problem among adolescents?.
Issues for 2nd ed. (2009)- cataloged as a serial in LC.
Includes bibliographical references..
Keywords: Adolescence; Adolescent psychology; Child development